Evaluation of Dyslipidemia among Hypertensive patients in Khyber Teaching Hospital, Pakistan - Muhammad Rahman, Atta Ullah, Shamaila Zahid, Sana, Muhammad Ilyas, Muhammad Zubair, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Dyslipidemia and hypertension are the major risk factors for cardiovascular disease. Both dyslipidemia and hypertension coexist in a single individual can double the risk of complication and a life threatening condition. No specific pattern of dyslipidemia reported among hypertensive patient. Therefore, this study was conducted to assess the correlation of dyslipidemia among hypertensive patients. Materials and Methods: A cross-sectional study was carried out in duration of six months in Peshawar. A total of 200 newly diagnosed patients or already taking antihypertensive medications were included. Blood samples were collected from all patients after taking verbally informed consent. Lipid profile was evaluated in blood sample and the collected data was analyzed through SPSS-21. Results: Among total 200 hypertensive patients, 59.5% (n=119) were male patients and 40.5% (n=81) female patients. Blood pressure (BP) were examined among all patients and the mean BP was 156/87. Hypertriglyceremia (TG>200mg/dl) was found in 32% (n=64/200) individuals, hypercholesterolemia (TC>200mg/dl) in 27% (n=54/200), and LDL (>100mg/dl) in 61.5% (n=123/200) hypertensive patients. High density lipid was found lower in 36.5% (n=73/200) hypertensive patients. Conclusion: The findings of this study shows that patients with hypertension are likely exhibit dyslipidemia including elevated triglycerides, total cholesterol and LDL level and have reduced HDL level. This study will help to make future plans for preventing both dyslipidemia and hypertension by both proper lifestyle changes and medical management.